Pemahaman tentang Nilai-Nilai Pancasila di Masyarakat Pedesaan Desa Gunung Perak Kecamatan Perak Kecamatan Sinjai Barat Kabupaten Sinjai - Auliah Andika Rukman (JED (Jurnal Etika Demokrasi), 2018)
The main problem in this study is how to understand the Pancasila Values in the community in Gunung Perak Village, West Sinjai District. This research aims to find out how the understanding of Pancasila Values in the community in Gunung Perak Village, Sinjai Barat District.The type of this research is that qualitative research with descriptive analysis method is used to examine the natural subject conditions and the research data is more concerned with interpretation of data found in the field. The results showed that the understanding of Pancasila values was still lacking, which was seen from the results of the study, namely 6 people who did not understand and 4 people who understood this occurred due to a lack of education levels in the past. The lack of public awareness about the values of the Pancasila needs to be carried out so that in the life of the community the value of the Pancasila is not merely a reading and noble values but increases people's understanding. Based on the results of the above research, it can be concluded that the understanding of Pancasila values in rural communities (Gunung Perak Village, West Sinjai District, Sinjai District) through qualitative research with descriptive methods of understanding has not been fully distributed.Keywords : Understanding, Pancasila Values, Society.